Original signs : gesture, sign, and the sources of language - Armstrong, David F. (Book collections on Project MUSE., 1999)
"Since Darwin's time, the majority of evolutionary linguists have theorized that language defines human beings and that speech defines language. In Original Signs, David Armstrong disputes the latter concept by showing that language has evolved in many different ways through many different paths, not just speech. The present evidence rests in the known fact that when deaf people sign, they are using a well-formed human language." "Armstrong addresses in turn the various thoughts on language development put forth by the major theorists, including Stephen J. Gould, Steven Pinker, Noam Chomsky, Terrence Deacon, and others, to finely hone his concept of the varied forms in which language developed."--Jacket